THE INFLUENCE OF LIVE STREAMING ON VIRTUAL EXPERIENTIAL MARKETING MEDIATED BY FOMO: A BIBLIOMETRIC ANALYSIS USING VOSVIEWER - Salimah, Salma; Rufaidah, Popy (Jurnal Bisnis dan Keuangan, 2025)
This study aims to propose a model that portrays the influence of live streaming through Fear of Missing Out (FOMO) on Virtual Experiential Marketing (VEM). The focus of this study is to highlight the dimensions involved in each variable that emerged from previous studies and find out the indicators related to the dimensions of live streaming, FOMO, and VEM. This study uses the Systematic Literature Review (SLR) method, which is then tested using Publish or Perish and Vosviewer software to explore new indicators of the dimension. In addition, this study utilizes Scopus, Science Direct, Emerald Insight, and other relevant journal databases to enhance the comprehensiveness of the literature review. The study discusses the findings of the similarities and differences of the dimensions that shaped the study's variables as well as the indicators to measure the dimensions of the variables. Therefore, this study proposes that the research model that exposes the influence of live streaming through FOMO on VEM can be applied by combining dimensions in the literature review and indicators from the results of the bibliometric map. The indicators to measure the above variables are: firstly, live-streaming is e-commerce, performance, and perspective; secondly, FOMO is a mental health role, social media fatigue, and addiction. Lastly, VEM is behavior, brand experience, and experiential marketing purchase intentions. This research contributes to a better understanding of the influence of live streaming through FOMO on VEM. This study applies marketing theory and consumer behavior in formulating managerial recommendations supported by empirical evidence.